Representation of LGBTQ Identity on Social Media: Multimodality Analysis on Instagram Account @yayasangayanusantara - Fitri Andika, Muhammad Fauzi; Indriastuti, Ana; Fithria, Khoirunnisa Nur; Hernanto, Pramudya Ardhika; Wijayanti, Tutik (UI Scholars Hub, 2024)
This research examines the representation of LGBTQ identity on Instagram using multimodal content analysis on the @yayasangayanusantara account. Using Muted Theory, this study highlights how LGBTQ identities are formed and presented in social and digital contexts. Instagram was identified as an essential platform for authentic and multidimensional LGBTQ identities by challenging conventional stereotypes and discrimination in traditional media. The research methodology involves qualitative analysis of various forms of content (text, images, and videos). The main focus is how LGBTQ individuals use social media to express themselves, seek support, and build solidarity. The findings show that Instagram is not just a passive means of interaction, but a robust advocacy and education tool. This research also highlights the role of social media in promoting inclusivity and a more positive understanding of the LGBTQ community. These findings challenge traditional assumptions regarding the silencing of minority groups, showing that they actively construct and negotiate their identities in digital public spaces. Theoretically, this research expands understanding of identity construction in the digital era and highlights the critical role of Instagram as an empowerment tool. Practically, these findings provide the basis for more effective advocacy strategies, more inclusive policies, and new approaches to education and social dialogue regarding LGBTQ issues in Indonesia.